Influence of Nano-Cutting Fluid in New Cutting and Forming Processes on Heat Transfer Performance of Mechanical Engineering - Wei Liu (International Journal of Analytical Chemistry)
In order to strengthen the thermal conductivity of green cutting fluid and the influence of nano-cutting fluid from new cutting and forming processes on heat transfer performance of mechanical engineering, a research method was proposed based on the influence of nano-cutting fluid from new cutting and forming processes on heat transfer performance of mechanical engineering. The dispersion stability, thermal conductivity, and viscosity characteristics of the nanofluid were studied, and the effects of acidification treatment time, type and concentration of carbon tube particles, surfactants, and testing conditions on the above properties were analyzed. It was found that the filling rate of T321 was about 25% when CNTs were filled, and the optimal compounding ratio of the two surfactants, sodium dodecyl benzenesulfonic acid (SDBS) and Tween-80 (TW-80), for the preparation of stable dispersed nanofluids was 3 ∶ 7. The optimum ratio of compound active agent to carbon tube is 5 ∶ 1. When CNTs were acidified for about 9 h and dispersed in sufficient and stable condition, the thermal conductivity of the base liquid was increased by 110% by the composite, and the shape factor of CNTs had the most significant effect on the thermal conductivity. It was found that the composite nanofluids had higher thermal conductivity and lower viscosity than the nanofluids prepared by ordinary CNTs. This was due to the fact that surfaces of CNTs were chemically modified during the opening and internal filling process, so that the composite had better dispersion stability in the base fluid.